Role of Stakeholder Participation in Governance of Rice Production in Kirinyaga County, Kenya - Njoroge, Francis Karanja (Human Resource and Leadership Journal, 2017)
Purpose: The purpose of the study was to examine the participation of key stakeholders in the governance of rice production in Mwea Irrigation Scheme (MIS) in Kirinyaga County in Kenya. Research Methodology: Data were also collected through interview of farmers and employees of National Irrigation Board and MIAD using a structured questionnaire. The questionnaire was tested using the Cronbach's Alpha Index and showed a high (+0.8) internal consistency and reliability. The study used multi-stage cluster sampling technique to select one zone from the five zones in MIS and randomly selected a sample of 50 farmers from the selected zone. The employees of National Irrigation Board and MIAD were clustered into management and field/technical staff and a purposive sample of 12 and 8, respectively, was drawn from each cluster. A sample of 60 respondents were interviewed. A time series model was used to generate a trend line for rice production. A regression correlation model, generated using SPSS Version 23, was used to analyze the relationship between variables. Findings: The findings showed that farmer participation in governance has a positive and significant relationship to rice production. Specifically, farmers' participation in governance has a positive linearly significant influence on rice production. Further, the study found that the governance role of NIB has a positive and significantly influence on rice production. Finally, the role of MIAD was found to be positively and significantly related to rice production. Specifically, the role of MIAD was found to have a positive linearly significant influence on rice production. The three key stakeholders considered explained a significant variation of 58 per cent in rice production, with NIB role explaining more followed by farmer participation and then MIAD. Recommendation: This study has shown that farmers' participation in governance of rice production has a positive and significant relationship with rice production. It is therefore recommended that their involvement in governance activities be structured so that their participation directly and indirectly through committees or their cooperative is deliberative and meaningful. This means that they participate in discussions, debates and presentations and in making decisions on substantive policy, and operational issues.